Presupposition projection from the scope of quantifiers: A novel approach - Kalomoiros, Alexandros (Proceedings of the Amsterdam Colloquium, 2025)
We present a modification of the Transparency Theory [5, 6], in the case of presupposition projection from the scope quantifiers, which allows the force of the quantifier to affect the force of the projected presupposition. The modification is based on letting the Transparency constraint operate on witness sets [1], and produces predictions that match currently known empirical results [3, 8], while also making novel predictions that will hopefully serve as input to future psycholinguistic experimentation.